The Role of Polish Local Ports on the Central Baltic Coast in the Development of Offshore Wind Farms - Weronika Kosek; Norbert Chamier-Gliszczynski; Waldemar Woźniak; Roland Jachimowski (Energies)
This paper examines the critical role of Polish local ports, particularly those on the Central Baltic coast, in the development of offshore wind farms. The study investigates how offshore wind energy development affects local port infrastructure, logistics, and the broader maritime economy while identifying opportunities and challenges arising from their integration into the offshore wind supply chain. To achieve this, a comprehensive methodological approach was employed, combining qualitive and quantitative analyses. The research utilized statistical data, policy documents, and spatial development plans to evaluate the current state of offshore wind energy projects in Poland. A specific focus was placed on assessing the infrastructure capabilities of local ports, including Kołobrzeg, Darłowo, Ustka, and Łeba, to serve as service hubs for offshore wind farm operations. Criteria such as waterway depth, quay length, storage facilities, and connectivity to transportation networks were analyzed in detail. Additionally, the study highlights the socio-economic benefits these ports can bring to the regions, such as job creation, economic revitalization, and enhanced regional competitiveness. The findings reveal that while these ports possess significant potential, strategic investments and modernization are essential to fully realize their role in supporting offshore wind energy. Recommendations are provided for policymakers, port authorities, and stakeholders to optimize the port’s development as part of Poland’s transition to renewable energy. This study contributes to broader discourse on renewable energy and maritime economic development, offering valuable insights into integrating small port infrastructure into large-scale energy projects.